Multifunctional metal oxides synthesized via a solvo-hydrothermal process for photocatalytic degradation of organic dye and bacteria in wastewater - Emile Salomon Massima Mouele; Htet Htet Kyaw; Myo Tay Zar Myint; Mohammed Al-Abri; Mohammed A.Al Belushi; Sergey Dobretsov; Jean-Luc Mukaba; Alechine Emmanuel Ameh; Leslie F. Petrik; Francis Ntumba Muya; Bernard Bladergroen; Kingsley Ehi Ebomah; et al. (Chemical Physics Impact)
The persistent occurrence of textile industrial dyestuff in water bodies has continuously threatened aquatic life and public health, requiring effective remediation. This study explores the solvo-hydrothermal synthesis of Ag2O, Fe2O3, AgFe2O3, TiO2, Ag-TiO2, Fe-TiO2, and AgFe-TiO2 catalysts. Various techniques, including SEM-EDS, FTIR, XRD, BET, TGA, and XPS characterized the as-prepared metal oxide (MO) catalysts. The multi-functionality of the catalysts was assessed on the degradation of Congo red dye and the inhibition of gram-positive B. subtilis in simulated wastewater. SEM analysis shows that MOs mostly appeared in granular morphologies except for Fe₂O₃, which comprised elongated grains, and showed that both Ag and Fe were successfully doped into the TiO₂ framework. The XRD survey revealed that Fe₂O₃ and TiO₂ were abundant in hematite and anatase phases. The BET findings indicated that the MOs are fine mesoporous particles, with TiO₂ showing the highest surface area of 83 m²/g, followed by 63, 28.27, and 24.03 m²/g for AgFe-TiO₂, AgFe₂O₃, and Ag-TiO₂, respectively. The antibacterial assays showed that Ag-TiO₂ and AgFe₂O₃ inhibited 58 % and 64 % of B. subtilis, correspondingly. The highest removals 98 and 99.99 % of Congo red (CR) dye were achieved with AgFe₂O₃ and TiO₂ after 5 h of irradiation time. At optimum conditions, AgFe₂O₃ and TiO₂ performed well and reached complete degradation up to 3 cycles. The outcomes of this study show that the multifunctional metal oxides produced via the solvo-hydrothermal method are thermally stable and can effectively be used for the simultaneous degradation of organic dye and disinfection of bacterial-polluted water.